Post-war laws affecting public agricultural education in the Philippines (1946-1963) - Delizo, Arsenia F. 1920- (s.n.], 1964)
This study looked into the provisions of the Republic Acts enacted by the Congress of the Philippines from its first session in 1946 to its last session in 1963. The full text of the laws, including the explanatory notes, was copied. The contents of the Republic Acts were analyzed to find out the objectives of the agricultural education. The provisions pertinent to the problem, quoted or paraphrased, were cited and interpreted in relation to the program of agricultural education as administered and organized by the Bureau of Vocational Education.